Det "okunniga museets" potential: Att möjliggöra alternativa lärmiljöer på Världskulturmuseet - Helen Arfvidsson (Dalarna university, 2022)
Based on the assumption that museums provide an alternative learning environment for school students, this study explores this assumption during two school visits at the National Museum of World Culture in Gothenburg. The aim is to generate knowledge about how these school visits constitute possibilities for such an environment by using the notion of the "ignorant museum" as well as a design-oriented perspective on learning. Interviews with the two accompanying teachers and the museum educators, as well as observations during the visits and a feedback session with the students following the visits, all contribute to the results. The main findings reflect the importance and uniqueness of the exhibition design, the museum educational approach and the museum artefacts which all contribute to possibilities of creating an alternative learning environment.